2011
DOI: 10.2174/1874415x01104010031
|View full text |Cite
|
Sign up to set email alerts
|

Hiding Charge in a Wormhole

Abstract: Existence of wormholes can lead to a host of new effects like Misner-Wheeler "charge without charge" effect, where without being generated by any source an electric flux arrives from one "universe" and flows into the other "universe". Here we show the existence of an intriguing opposite possibility. Namely, a charged object (a charged lightlike brane in our case) sitting at the wormhole "throat" expels all the flux it produces into just one of the "universes", which turns out to be of compactified ("tube-like"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 58 publications
(132 reference statements)
0
8
0
Order By: Relevance
“…In previous publications it has been shown that this phenomenon takes place in a gravity/gauge-field system self-consistently coupled to a charged lightlike brane as a matter source, where the gauge field subsystem is of a special non-linear form containing a square-root of the Maxwell term [1]. The latter has been previously shown [16]- [20] to produce a QCDlike confining ("Cornell" [23]- [25]) potential in flat space-time.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…In previous publications it has been shown that this phenomenon takes place in a gravity/gauge-field system self-consistently coupled to a charged lightlike brane as a matter source, where the gauge field subsystem is of a special non-linear form containing a square-root of the Maxwell term [1]. The latter has been previously shown [16]- [20] to produce a QCDlike confining ("Cornell" [23]- [25]) potential in flat space-time.…”
Section: Introductionmentioning
confidence: 92%
“…In contrast to the Misner and Wheeler effect, the charge-hiding effect by a horned particle means a genuinely charged matter source of gravity and electromagnetism may appear electrically neutral to an external observer. In previous publications, it has been shown that this phenomenon takes place in a gravity/gauge-field system self-consistently coupled to a charged LLB as a matter source, where the gauge-field subsystem is of a special nonlinear form containing a square root of the Maxwell term [1]. The latter has been previously shown [16][17][18][19][20] to produce a QCD-like confining ('Cornell' [23][24][25]) potential in flat spacetime.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Studying such metamaterial space configurations also appears interesting in light of recent demonstrations that two colored quasiparticles (quarks) in maximally supersymmetric Yang-Mills theory entangled in a color singlet EPR pair are connected by a wormhole [15,16], and that the physical vacuum appears to exhibit hyperbolic metamaterial properties when subjected to a very strong magnetic field [17]. In addition, such effects as Misner-Wheeler "charge without charge" [18] and the recently proposed charge-hiding effect [19] may be replicated in the metamaterial system. Indeed, as obvious from Fig.3, coupling of some of the L=0 mode power into the wormhole leads to appearance of opposite effective charges of the wormhole openings due to non-zero S 3 near the openings.…”
mentioning
confidence: 99%